Core Loss Measurement of Somaloy 700 Material Under Round Loci of Magnetic Flux Density - Rohanim Asari, Ashraf; Guo, Youguang; Zhu, Jianguo (International Journal of Engineering and Technology, 2018)
The magnetic properties of SOMALOY 700 material are aggressively studied by some researchers in predicting the production of total core loss during the magnetization process of that particular material. Core loss is resulted due to the alternating and rotating magnetic fields in a core material.Â  The magnetic properties of SOMALOY 700 material is studied in this paper since it offers the low core loss during the operation. 2-D measurement were conducted by controlling the fluxes to be circular with the help of LabVIEW while the core loss calculations were calculated by MathCAD. The performance of SOMALOY 700 material at different frequencies were compared. The finding indicates that the magnetization at 1000 Hz contributes higher core loss compared to the magnetization at 500 Hz and 50 Hz. The details of SOMALOY 700 material provide good information to practitioners in designing electrical machine at different variation of frequencies.Â Â